Christoph Heilig, The Apostle and the Empire. Paul’s Implicit and Explicit Criticism of Rome (Grand Rapids, MI: Eerdmans 2022) - Kowalski, Marcin (The Biblical Annals, 2023)
Book Review: Christoph Heilig, The Apostle and the Empire. Paul’s Implicit and Explicit Criticism of Rome (Grand Rapids, MI: Eerdmans 2022). Pp. 192 + xxii. ISBN 978-0-8028-8223-3